Prognostic significance of lactate dehydrogenase and its impact on the outcomes of gastric cancer: a systematic review and meta-analysis - Chen, Jinjin; Zou, Xiaoyue (Frontiers in Oncology, 2023)
Background: The prognostic significance of lactate dehydrogenase (LDH) and its impact on the outcomes of gastric cancer (GC) is still unclear. We assessed the link between the levels of LDH and the overall survival (OS) and disease-free survival (DFS) in GC patients. Methods: A comprehensive search (both electronic and manual) was carried out in PubMed via MEDLINE, Web of Science (WoS), Experta Medical Database (Embase), and CENTRAL (Cochrane Library) databases for citations that evaluated the strength of association between LDH cut-off levels and OS and/or DFS in GC. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using a random-effects model, and heterogeneity was assessed. Results: Eighteen studies with 5328 patients were included in our review. The overall pooled HR for OS was 1.48 (95% CI: 1.22-1.80) with high heterogeneity (I2 = 86%). Subgroup analyses showed that the link between LDH and OS was more prominent in Caucasian (HR 1.50 95% CI [0.80, 2.81], p=0.21) than in Asian cohorts (HR, 1.51 95% CI [1.21, 1.87], p=0.002). No significant overall association between LDH and OS (HR = 1.12, 95% CI: 0.76-1.65, p = 0.58) was found. Similar subgroup analyses results were reported for the association between LDH and DFS. Conclusion: In patients with GC, elevated LDH levels may correlate with worse OS and DFS, but the association is not significant. LDH is a significant predictor of OS but not of DFS. Further studies with larger sample sizes and more standardized criteria for defining elevated LDH levels are needed to confirm our findings.